Dynamic discovery and maintenance of role-based performance standards - Ramón Hermoso (2012)
Standards have been deeply studied in economics in order to assure a certain quality of service in bilateral contracts. More specifically, in multi-agent systems performance standards may be used in order to articulate contracts among partners in environments dealing with uncertainty. However, little effort has been made on defining how standards are created and, what is more important, how to ensure standards compliance over time. In this work we put forward a mechanism that, on one hand, creates standards from roles denoting task specialization skills and, on the other hand, tries to maintain role performance standards by applying incentives and/or punishments to agents identified as being able to play those roles.